Polymorphonuclear leukocyte and monocyte activation induced by plasma from patients with heparin-induced thrombocytopenia in whole blood - Khairy, Mahnouch; Lasne, Dominique; Amelot, Aymeric; Crespin, Malvina; Rendu, Francine; Aiach, Martine; Bachelot-Loza, Christilla (Thrombosis and Haemostasis, 2004)
Heparin-induced thrombocytopenia (HIT), a severe complication of heparin therapy, results from platelet activation by heparin-dependent antibodies. Previously, we have shown that plasma from patients with HIT (HIT plasma) induces leukocyteplatelet aggregation in blood. In this report, we examined leukocyte activation by HIT plasma and the contribution of heparin and platelets to this activation, in whole blood. Degranulation of leukocytes from HIT patients was evaluated as a leukocyte activation marker. We showed that polymorphonuclear leukocytes (PMN) and monocytes were the leukocyte subpopulations involved in platelet-leukocyte aggregation induced by HIT plasma in healthy donor blood. PMN and monocyte activation, reflected by increased surface expression of the CD11b adhesion molecule, was induced by HIT plasma in a heparin-dependent manner. The CD11b increase induced by HIT plasma was observed on PMN only when they were associated with platelets. Moreover, the increased CD11b expression on monocytes and PMN correlated strongly with the degree of platelet adhesion to these cells. Degranulation of leukocytes from HIT patients and control subjects (non-HIT heparin-treated patients and healthy subjects) was evaluated in vivo by measuring the plasma myeloperoxidase concentration. HIT plasma contained higher myeloperoxidase concentrations than control plasma, suggesting leukocyte degranulation during HIT. In conclusion, this study provides the first evidence that PMN activation is induced by HIT plasma. HIT plasma induced PMN and monocyte activation in a heparin-dependent manner. In whole blood, platelet association with monocytes and PMN, and the activation of these leukocytes by HIT plasma were interrelated. Finally, leukocyte degranulation could be involved in HIT physiopathology.
Keywords: Heparin-induced thrombocytopenia; leukocyte; activation; platelet